The effects of husband and wife job resources on child happiness at home: the crossover of positive experience - Muhamad Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2022)
Research to date has empirically supported that job resources influence employees’ well-being. However, investigations remain scarce on gaining an understanding of the possible consequences of job resources on employees’ children at home. Using a crossover perspective, specifically, we examine the effects of job resources on employees’ positive outcomes (i.e., happiness and work engagement), and how this crosses over to their children. In Sample 1, 141 dyads (husbands and children) participated while Sample 2 involved participation by 96 dyads (wives and children). Results of mediation analysis show that husband’s work engagement crossed over to children’s happiness through husband’s happiness (Sample 1). But the study did not found the mediation effect for wife-child sample (Sample 2). These studies have integrated the crossover model in the family context by including children as one of the main actors in the crossover process.